Kualitas Produk: Analisis Produk Minuman Kopi di Cafe Agam Pisan Palembang - Lesmana, Andhika Chandra; Julvirta, Enos (Manajemen dan Pariwisata, 2025)
Product quality is an effort to meet or even exceed customer expectations. One of the most common crops in Indonesia is coffee. The high consumption of coffee is driven by the extensive development of cafes, especially in Palembang City. Encouraging business owners to be more creative in making beverage products that they offer to customers. Agam Pisan Café is one of those cafes, and this place not only sells coffee beverage products, but also produces its own coffee beans. This study was conducted to analyze the quality of coffee drinks at Agam Pisan Café based on aroma, acidity, body, flavour, aftertaste, and sweetness on 3 populer drinks. The method used is a verification descriptive method with a percentage model. Data collection techniques are obtained through observation, interviews, questionnaires, documentation studies, and literature studies. The results showed that the product quality of creamy aren coffee drinks reached 67.28%, in the "appropriate" category, the product quality of creamy matcha expresso drinks reached 59.83%, in the ‘sufficient’ category, and the product quality of avocado coffee drinks reached 62.78%, in the “appropriate” category.